BIOCOMPATIBLE P(TM co SA-CAA) HYDROGELS WITH pH RESPONSIVE AND ENHANCED MECHANICAL PERFORMANCE - Gustini, Gustini; Kaprawi, Kaprawi; Basri, Hasan; Irmawan, Irmawan; Yani, Irsyadi; Paramita Eka Utami, Nurhabibah (Politeknik Negeri Sriwijaya, Indonesia, 2023)
In recent years, development of hydrogel that combines biocompatibility, pH responsive and mechanical performance has attracted the attention of researchers. A novel biocompatible hydrogel, composed of P(TM co SA) and P(TM co CAA) was synthesized by a simple admixture and heating process. The results show that with increasing levels of SA-CAA monomer concentration, an increase in tensile strength and elongation at breakpoint was observed and optimal at the ratios P(TM co SA CAA). Tensile strenght and young’s modulus registered an impressive increase of 43% and 40% respectively. These improvements are attributed to strong synergistic hydrogen bonding interactions between the TM and SA-CAA chains. During the experiment, maximum increase in weight was also achieved at pH 10 NaOH solution, it is show the pH-responsive hydrogels. The investigation of P(TM co SA-CAA) hydrogel mechanism showed that more homogenous dispersed through crosslinks dominated by β-sheets from Amide I structures. Furthermore, the SA-CAA molecules contributed to the biocompatibility, pH responsive and mechanical performance of P(TM co SA-CAA) hydrogels. Conclusively, its P(TM co SA-CAA) hydrogels clearly demonstrated the relevance of the provide a bioresponsive material for biomedical applications, such as tissue engineering, regenerative medicine and pH-sensitive drug delivery.